Case Report: A rare case of acute herbicide poisoning induced pediatric acute osteofascial compartment syndrome - Shi, Xueping; Wang, Xin; Guo, Pei (Frontiers in Pediatrics, 2025)
Acute osteofascial compartment syndrome (AOCS) is rarely seen in patients with acute herbicide poisoning, and no cases have been reported in children. The correct treatment approach is of vital importance. We report a case of a 13-year-old girl who was admitted to our hospital 17 h after oral ingestion of “diquat” (a herbicide), and developed clinical symptoms of AOCS 21 h later. The girl was treated with measures such as removing the toxins, using mannitol for dehydration, and elevating the affected limb. The patient's AOCS progressed relentlessly; on hospital day 4, after failure of conservative management, she underwent decompressive surgical fasciotomy (DSF) of the lower legs. The girl responded well to continuous renal replacement therapy (CRRT) and continuous fascial decompression treatment. On hospital day 25, she underwent debridement and suture surgery on both lower legs. At discharge, the girl's lower legs bilateral suture incisions were healing well, and the affected legs could stand. Two months later, the girl was able to walk independently.